2020
DOI: 10.1186/s12876-020-01378-w
|View full text |Cite
|
Sign up to set email alerts
|

Late stage diagnosis of mucinous adenocarcinoma of the appendix: a case report of an unusual tumor with a rare presentation

Abstract: Background: The incidence of mucinous appendiceal adenocarcinomas (MAA) has increased over the past three decades. Advanced stage tumor diagnosis is likely attributable to non-specific findings. Here we describe advanced stage appendiceal MAA presenting as inguinal ulcers, scrotal abscesses, and other nonspecific symptoms. To our knowledge, this is the first report of MAA presenting as inguinal pain with inflamed phlegmonous tissue and scrotal abscess. Case presentation: A 67-year-old male presented to a rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Roma et al 13 reported a late‐stage diagnosis of appendiceal mucinous adenocarcinoma with a rare presentation, such as scrotal pain, abscess, and inguinal drainage, but our patient developed with typical symptoms, like abdominal pain, weight loss, and palpable mass, without any appendicitis alarm.…”
Section: Discussionmentioning
confidence: 57%
“…Roma et al 13 reported a late‐stage diagnosis of appendiceal mucinous adenocarcinoma with a rare presentation, such as scrotal pain, abscess, and inguinal drainage, but our patient developed with typical symptoms, like abdominal pain, weight loss, and palpable mass, without any appendicitis alarm.…”
Section: Discussionmentioning
confidence: 57%
“…With an incidence rate of 37%-38% among all appendiceal cancers reported, mucinous adenocarcinoma is the most prevalent subtype of primary adenocarcinoma with a mean age of presentation at 60 years of age, no explicit sex predilection, and no known risk factors [2][3][4]. Furthermore, MAA is further classified as low and high grade, which is essential in deciding the treatment options and predicting the prognosis [2].…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal malignancies are a rare group of tumors usually found incidentally during appendectomy [1]. Adenocarcinoma is the most predominant type of primary appendix cancer, comprising 60% of all cases, and mucinous adenocarcinoma of the appendix (MAA) is the most prevalent subtype of primary adenocarcinoma with an incidence rate of 37%-38% among all appendiceal cancers [2][3][4]. In terms of clinical presentation, in over 50% of cases of appendiceal cancer, the patient is asymptomatic, and the malignancy is detected incidentally [1].…”
Section: Introductionmentioning
confidence: 99%
“…MAA is difficult to diagnose due to the non-specific nature of early symptoms, including lower abdominal pain, weight loss, nausea, vomiting, a palpable mass, and acute appendicitis, and is frequently misdiagnosed as a gynecological condition such as right adnexal mass[ 7 ]. The bladder may also be affected, with symptoms of bladder irritation or the formation of hematuria, leading to a misdiagnosis of urinary tract infection or bladder cancer[ 8 - 10 ]. In most cases, appendiceal malignancy is detected accidentally by abdominal CT or surgery for appendicitis due to other reasons.…”
Section: Discussionmentioning
confidence: 99%